Personality Dynamics Of Adolescent Durgs Users During The Rehabilitas Procces At Ciamis Bnnk In 2026 - Siti Nurjanah; Didin Solehuddin; Ahmad Gojin; Yandi Cahya Yundani (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
This study aims to analyze the personality dynamics of adolescent drug users undergoing rehabilitation at the Ciamis National Narcotics Agency (BNNK). The background of this study is based on the increasing number of drug abuse cases among adolescents, particularly high school students (SMA), which impacts their psychological well-being and personal development, ultimately impacting their future. The method used in this study is qualitative with a phenomenological approach. The subjects consisted of high school adolescents undergoing rehabilitation. Data collection techniques were conducted through in-depth interviews with one of the clients undergoing rehabilitation at the Ciamis BNNK. Observation and documentation were used.